2016
DOI: 10.4317/jced.53196
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological analysis of a series of periapical cysts and periapical granulomas diagnosed in a Brazilian population

Abstract: BackgroundPeriapical cysts (PC) and periapical granulomas (PG) are the two most common chronic inflammatory periapical diseases, but their clinicoradiological characteristics can vary depending on the methods employed in each study. The aim of the present work was to analyze the clinical and radiological profile of a series of PC and PG diagnosed in a Brazilian population.Material and MethodsThe files of two Oral Pathology laboratories were reviewed and all cases diagnosed as PG and PC were selected for the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
3
9
0
4
Order By: Relevance
“…The results also showed statistically significant mean student's score in group I receiving the program CD containing the images with MCQ after lecture compared to the other group II. This results is beneficial in the field of diagnosis and it is in accordance with the prevalence of this lesion as Tavares et al (2017) [34] were concluded that periapical granulomas were most frequently diagnosed from biopsies submitted by endodontist following apical surgery followed by radicular cyst, scars and other diagnoses.…”
Section: Discussionsupporting
confidence: 65%
“…The results also showed statistically significant mean student's score in group I receiving the program CD containing the images with MCQ after lecture compared to the other group II. This results is beneficial in the field of diagnosis and it is in accordance with the prevalence of this lesion as Tavares et al (2017) [34] were concluded that periapical granulomas were most frequently diagnosed from biopsies submitted by endodontist following apical surgery followed by radicular cyst, scars and other diagnoses.…”
Section: Discussionsupporting
confidence: 65%
“…Nonetheless, it can be substantially underreported, considering the number of periapical surgical specimens that are not submitted to histopathological analysis after removal, as well as the differences on reporting these lesions by different oral pathology laboratories. Using previous published data of the same oral pathology laboratory (17), prevalence of PA could be estimated in less than 1% of all periapical lesions submitted to histological examination in our series. More likely, authors have characterized PA when sulfur granules with the Splendore-Hoeppli phenomenon are present, which consists in eosinophilic material around filamentous gram-positive colony-forming aggregates surrounded by inflammatory cells, probably composed of antigen-antibody complex, tissue debris and fibrin.…”
Section: Discussionmentioning
confidence: 85%
“…Hasil yang tidak jauh berbeda dengan penelitian yang dilakukan sebelumnya menunjukan bahwa daerah yang paling sering terjadi lesi periapikal adalah anterior rahang atas dan posterior rahang bawah. 6,9,16,17 Lesi periapikal pada daerah anterior maksila yang predominan menurut Berlinck & Monnerat pada tahun 2015 terjadi karena morfologi serta lokasi dan tingginya insidensi trauma sehingga mengarah pada resiko nekrosis pulpa yang lebih tinggi daripada regio posterior. 9,17 Posterior rahang bawah menjadi lokasi terbanyak kasus lesi periapikal karena gigi posterior memiliki permukaan oklusal yang berbeda, dimana gigi posterior memiliki pit and fissure yang lebih dalam sehingga sisa makanan sulit untuk dibersihkan.…”
Section: Tahun 2009unclassified